The Principles of Language Learning - Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2015)
In this era, becoming bilingual or multilingual is a way of life. Thus, learning a foreign language, which is a complex process, is badly needed. Knowing the principles of language learning will facilitate the language learners to master the second language. There are two pathways to develop competence in a language: language acquisition and language learning. There are several hypotheses about second language acquisition, i.e. the natural order hypothesis, the monitor hypothesis, the input hypothesis, the affective filter hypothesis. In order to be successful in language learning, language learners must have certain characteristics. The personality variables or factors that play great role in the success or failure of language learning are as follows: 1) extroversion and introversion, 2) tolerance of ambiguity, 3) empathy/ego permeability and sensitivity to rejection, 4) cognitive style and field dependence/independence. Key words: language acquisition, language learning, language competence, the monitor hypothesis, the input hypothesis, the affective filter hypothesis, personality variables